2001
DOI: 10.1037/0735-7044.115.1.243
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid modulation of time estimation in the rat.

Abstract: Cannabinoids have been implicated in a variety of cognitive processes in humans, including attention, learning, memory, and time estimation. However, studies of the effects of cannabinoids on rodent behavior have focused on motor, learning, and memory tasks. To assess cannabinoid effects on time perception, this study examined whether systemically administered cannabinoid receptor agonists and a cannabinoid receptor antagonist influenced rats' performance of a time interval estimation task based on a fixed-int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 9 publications
3
25
1
Order By: Relevance
“…Similar observations are observed in preclinical studies. In accordance with Han and Robinson (2001), in the present study we found that treating rodents with the cannabinoid receptor agonist WIN 55 212-2 shortened the response interval in an FI task, effectively leading animals to show a premature acceleration in the temporal response pattern.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Similar observations are observed in preclinical studies. In accordance with Han and Robinson (2001), in the present study we found that treating rodents with the cannabinoid receptor agonist WIN 55 212-2 shortened the response interval in an FI task, effectively leading animals to show a premature acceleration in the temporal response pattern.…”
Section: Discussionsupporting
confidence: 67%
“…Immediately following reinforcement, responding slows before accelerating to a maximal terminal rate at the culmination of the interval (Dews, 1970). Cannabinoids, like other drugs that speed up the internal clock, produce an accelerated temporal response pattern (Cheng et al, 2007;Han and Robinson, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…High densities of CB 1 receptors are also present in frontal cortical and striatal regions (Egertova and Elphick 2000; Tsou et al 1998), suggesting involvement of the endocannabinoid system in executive functions that appear to be largely controlled by frontal corticostriatal systems (for review, see Miller and Cohen 2001). Indeed, several clinical and preclinical observations have demonstrated that Δ 9 -tetrahydrocannabinol (THC), the principle active cannabinoid of Cannabis sativa and other synthetic cannabimimetics impair selective attention (Arguello and Jentsch 2004; Solowij et al 1995; Verrico et al 2004) and behavioral flexibility (Egerton et al 2005; Hill et al 2006), alter time estimation (Han and Robinson 2001, McDonald et al 2003), and impair working memory (Ilan et al 2004; Jentsch et al 1997). Nonetheless, to date, little is known about the involvement of the endocannabinoid system in other executive functions such as inhibitory control processes subserving impulsivity.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with this consequence of the pro posed mechanism, time was shown to flow more slowly for marijuana smokers [65,66]. Rodents treated with cannabinoids also underestimated intervals with dura tions of 10 and 30 s [64,67].…”
Section: Effects Of Opioids and Cannabinoidsmentioning
confidence: 69%
“…The possibility of the alteration of the frequency of the "internal clock" in the presence of cannabinoids has been shown earlier [64]; however, the mechanisms of this effect were not analyzed. We believe that can nabinoids may influence time perception not only via dopamine release but also indirectly via modulation of inputs to neurons of the prefrontal cortex, which has a high density of cannabinoid CB1 receptors [63].…”
Section: Effects Of Opioids and Cannabinoidsmentioning
confidence: 98%